Infographics: An Effective Tool for Modern Learning in Indonesia - Abroriah, Hasna; Wahyuni, Reti (Universitas Indraprasta PGRI, 2024)
This research aims to explore the effectiveness of infographics in learning in higher education, as well as the challenges and perceptions of students. A qualitative method was conducted in the research, and employing the structured interviews that involving UIN Walisongo students who applied infographics in their learning. The research results revealed that infographics increase student’s understanding and engagement, with image and color visualization that assisted in elevating the absorption of information. The challenges found were infographic designs that were dense or less structured. The findings recommend to display in simple, clear design and concise text. In conclusion, infographics are effective in conveying complex material.